The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1975
DOI: 10.1104/pp.55.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of in Vivo Conversion of Methionine to Ethylene by l-Canaline and 2,4-Dinitrophenol

Abstract: L-Canaline, a potent inhibitor of pyridoxal phosphate-mediated reactions, markedly inhibited the conversion of methionine to ethylene and carbon dioxide by apple tissue. A 50% inhibition of methionine conversion into ethylene was obtained with 50 jtM canaline and almost complete inhibition with 300 AM canaline. When 2, 4-dinitrophenol, an oxidative phosphorylation uncoupler, was fed to apple tissue, it inhibited the conversion of radioactive methionine to ethylene by 50% at a concentration of 60 AM and by 90% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
1

Year Published

1979
1979
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 22 publications
1
24
0
1
Order By: Relevance
“…Inhibitors of pyridoxal phosphate-mediated enzymic reactions which are known to inhibit C2H4 production in various tissues ( 15,16) did not affect the conversion of ACC to C2H4 in bean-leaf discs (Table III). However, addition of pyridoxal phosphate to the incubation medium inhibited C2H4 production about 20% within 2 h. Similar data were recently reported elsewhere (9).…”
Section: Resultsmentioning
confidence: 99%
“…Inhibitors of pyridoxal phosphate-mediated enzymic reactions which are known to inhibit C2H4 production in various tissues ( 15,16) did not affect the conversion of ACC to C2H4 in bean-leaf discs (Table III). However, addition of pyridoxal phosphate to the incubation medium inhibited C2H4 production about 20% within 2 h. Similar data were recently reported elsewhere (9).…”
Section: Resultsmentioning
confidence: 99%
“…As indicated below, ethylene is generally synthesized from methionine, which is the most common precursor of this hormone in plants (16), through a series of steps involving S-adenosylmethionine (SAM) and ACC (4): methionine -+ SAM ACC --ethylene (4,15). Several inhibitors acting at different points in this pathway have been described, notably rhizobitoxine and its analogs (17), L-canaline (20), and benzylisothiocyanate (21). Because of this knowledge, experiments were designed with the purpose of elucidating the role of endogenous ethylene in the accumulation of HRGP, into the cell wall, in diseased plants.…”
Section: Discussionmentioning
confidence: 99%
“…L-Can (Sigma), benzylisothiocyanate (Fluka), and aminoethoxyvinylglycine (Hoffman-La Roche) were used as inhibitors (17,20,21) of ethylene synthesis, and I-aminocyclopropane-l-carboxylic acid (Sigma) as a precursor of ethylene (4). LCan was prepared from L-Can dipicrate before each experiment by filtration through a column (5 x I cm) of Dowex AG 2 x 8, 200-400 mesh, Cl-form, in water as reported by Murr and Yang (20). The recovered L-Can was measured according to Yemm and Cocking (29) and adjusted to a suitable concentration with H20.…”
Section: )mentioning
confidence: 99%
“…1 and 10). Recently, S-adenosylmethionine was proposed as an intermediate in the conversion of methionine to ethylene in apple tissue (3,9). Results of Hanson and Kende (5) indicated that ethylene production in flower tissue of Ipomoea tricolor might be dependent on methionine derived from SMM3 and homocysteine.…”
mentioning
confidence: 99%